Caracterización morfométrica e índices corporales de caprinos criollos del Oeste de Santiago del Estero - Cordoba, Alicia Beatriz; Contreras, Marcelo Cesar; Piedrasanta, Rafael Osvaldo; Lazarte, Marcelo Alonso; Pisano, Paolo; Llorvandi Salim, Carlos Maria (Asociación Argentina de Producción Animal, 2025)
Ponencia y póster